ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRESTASI BELAJAR AKUNTANSI - Immaculata Herawati; Yuli Widiastuti (Universitas Negeri Malang, 2013)
Abstract: The purpose of this research is for determining the factors that influence student achievement in accounting class XI IPS SMA Negeri 1 Malang and the most dominant factor Â influencing accounting student achievement. The research did in SMA Negeri 1 Malang and research subjects are students of class XI-IPS SMA Negeri 1 Malang academic year 2012/2013. Kind of this research are descriptive and instruments that used in the form are questionnaires and documentation. While the technique of data analysis used Pearson Product Moment for validity, Alpha Cronbanch to test reliability, and factor analysis using SPSS 16 for windows to find out what factors are affecting the achievement of accounting subjects. From the data analysis result is known that the factors affecting accounting students learning achievement are motivation, social environment consisting of the relations among members of the family and student relationships with students, psychology consisting of EQ, study habits, attention, individual modernity, as well as the attitude and readiness IQ factors. Abstrak: Penelitian ini bertujuan untuk mengetahui faktor-faktor yang mempengaruhi prestasi belajar akuntansi siswa kelas XI IPS SMA Negeri 1 Malang dan faktor yang paling dominan dalam mempengaruhi prestasi belajar akuntansi siswa. Penelitian ini dilakukan di SMA Negeri 1 Malang, dan subjek penelitiannya adalah siswa kelas XI IPS SMA Negeri 1 Malang tahun ajaran 2012/2013. Jenis penelitian ini adalah deskriptif dan instrumen yang digunakan berupa kuisioner dan dokumentansi sedangkan teknik analisis datanya menggunakanÂ Pearson Product Moment untuk uji validitas,Â Alpha Cronbanch untuk uji reliabilitas, dan analisis faktor menggunakan SPSS 16 for window untuk mengetahui faktor-faktor yang mempengaruhi prestasi belajar akuntansi. Dari hasil analisis data diketahui bahwa faktor-faktor yang mempengaruhi prestasi belajar akuntansi siswa yaitu motivasi, lingkungan sosial yang terdiri dari relasi antaranggota keluarga dan relasi siswa dengan siswa, psikologi yang terdiri dari EQ, kebiasaan belajar, perhatian, modernitas individu, sikap dan kesiapan serta faktor IQ.